Expression of plasma vascular endothelial growth factor in patients with hepatocellular carcinoma and effect of transcatheter arterial chemoembolization therapy on plasma vascular endothelial growth factor level - Li, Xin (World journal of gastroenterology : WJG, 2004)
To investigate the expression level of plasma vascular endothelial growth factor (P-VEGF) in patients with hepatocellular carcinoma (HCC) and its relationship with the clinicopathologic characteristics, and to examine the changes of P-VEGF in the course of transcatheter arterial chemoembolization (TACE). Peripheral blood samples were taken from 45 HCC patients before and 1, 3, 7 d, and 1 mo after TACE. Plasma VEGF level was measured with the quantitative sandwich enzyme-linked immunosorbent assay (ELISA). Twenty patients with benign liver lesions and 17 healthy control subjects were also included in this study. Plasma VEGF levels in HCC patients were significantly elevated as compared to those in patients with benign liver lesions (P = 0.006) and in the normal controls (P = 0.003). Significant differences were observed when P-VEGF was categorized by tumor size (P = 0.006), portal vein thrombosis (P = 0.011), distant metastasis (P = 0.017), arterial-portal vein shunting (P = 0.026), and International Union Against Cancer (UICC) TNM stage (P = 0.044). There was no correlation between plasma level of VEGF and the level of alpha fetoprotein (alpha-FP) (r = 0.068, P = 0.658) and weakly correlated with the number of platelets (r = 0.312, P = 0.038). P-VEGF levels increased significantly and reached the peak value on the first day after TACE, and then decreased gradually. The change rate of P-VEGF concentration (one month post-TACE/pre-TACEX100%) was correlated with the retention rate of lipiodol oil (r s = 0.494, P = 0.001) and the tumor volume change (r s = 0.340, P = 0.034). The patients who achieved a partial or complete response to TACE therapy showed significantly less pre-treatment P-VEGF than those nonresponders (P = 0.025). A high pre-therapeutic P-VEGF level was associated with poor response to treatment (P = 0.018). A high pre-treatment P-VEGF level is a useful marker for tumor progression, especially for vascular invasion. TACE increases the level of P-VEGF only temporarily which may be associated with tumor ischemia. P-VEGF may be useful in predicting treatment response, monitoring disease course after TACE and judging the effect of different TACE regimens.